Saturday
March 25, 2017

Post a New Question

Posted by on .

Solve for x: log3(x^2-4)-log3(x+2)=2

  • math - ,

    log3(x^2-4)-log3(x+2)=2
    log3 [(x^2-4)/x+2)] = 2
    log3 [(x+2)(x-2)/(x+2)] = 2
    log3 (x-2) = 2
    x-2 = 3^2
    x = 11

  • math - ,

    log3 (x^2-4) -log3 (x+2)=2
    log3 [(x^2-4)/x+2)] = 2
    log3 [(x+2)(x-2)/(x+2)] = 2
    log3 (x-2) = 2
    x-2 = 3^2
    x = 11

  • Adam - math - ,

    Adam, why would you just cut-and-paste my solution and claim it as yours ?

    You didn't even bother to fix my error in the 2nd line, where I missed a bracket.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question